Design of a monostable multivibrator with on-chip delay time control - Subramanian Harihara Venkata Ramanan. (2008)
Explores a solution to combat the challenge of generating various ranges of pulse duration outputs by the use of an On-Chip circuit, which replaces the resistor component in the Monostable multivibrator.